2008
DOI: 10.1177/1076029608326167
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Thrombelastography in the Monitoring of Acquired Factor VIII Inhibitor Hemophilia A: Report on a 78-year-old Woman With Life-threatening Bleedings

Abstract: A 78-year-old woman was admitted to our hospital because of syncope associated with hematomas in both legs. Acquired hemophilia A (AHA) with a low antifactor VIII antibodies activity was diagnosed. Whole blood (WB) thrombelastographic profile depicted a hypocoagulable state. During hospitalization, the patient experienced life-threatening bleedings in the neck and in the right thigh. FVIII concentrates and rFVIIa was safe and effective in controlling acute hemorrhagic symptoms. Immunosuppressive therapy was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Ideally, TEG would be used in the monitoring of change within an individual rather than to obtain a diagnostic measurement related to a general reference range. Several preanalytical and postanalytical factors can affect the TEG trace including age, sex, 9 and hematocrit; 10 native whole blood versus citrated; type of sample modifier such as kaolin, tissue factor 11 or corn trypsin inhibitor; the presence of heparin when blood is withdrawn from indwelling lines; and pH and temperature during the assay. 12 The article also discusses the interpretation of TEG in the context of various clinical and pathological conditions including blood component therapy, antiplatelet drug therapy, monitoring heparin and fibrinogen administration, in addition to the use of the assay in monitoring hemostasis in liver disease, trauma, and obstetrics.…”
mentioning
confidence: 99%
“…Ideally, TEG would be used in the monitoring of change within an individual rather than to obtain a diagnostic measurement related to a general reference range. Several preanalytical and postanalytical factors can affect the TEG trace including age, sex, 9 and hematocrit; 10 native whole blood versus citrated; type of sample modifier such as kaolin, tissue factor 11 or corn trypsin inhibitor; the presence of heparin when blood is withdrawn from indwelling lines; and pH and temperature during the assay. 12 The article also discusses the interpretation of TEG in the context of various clinical and pathological conditions including blood component therapy, antiplatelet drug therapy, monitoring heparin and fibrinogen administration, in addition to the use of the assay in monitoring hemostasis in liver disease, trauma, and obstetrics.…”
mentioning
confidence: 99%
“…Using ROTEM, doctors were able to detect a hypocoagulable state in an elderly woman who experienced life‐threatening bleedings during surgery. From the thromboelastogram, it was determined that the woman had developed acquired haemophilia A as seen by the decreased MCF and increased CT. FVIII treatment and continued monitoring of the woman's coagulability were able to successfully increase her MCF and decrease her CT .…”
Section: Macroscale Biomechanics In Haemostasismentioning
confidence: 97%
“…Results from several studies using TEG/ROTEM showed that patients with haemophilia had much longer clotting times, lower maximal amplitude indicating decreased clot stiffness and slower clot initiation times [37][38][39][40][41][42][43][44][45]. In a study by Ghosh et al, it was found that TEG could be used to characterize different subgroups of patients with haemophilia between those demonstrating hypercoagulable patterns, hyperfibrinolytic patterns, inability to form clots and variable clot initiation times.…”
Section: Haemophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…• rFVIII prophylaxis 67,70,76,79 • rFVIIa 68,71,80,81 • aPCC 80 • Emicizumab 67,78 • PLT infusion 82 Hemophilia A with inhibitors R: 84,86,88,89 MA: 83,84,86,88,89 G: NM 84,89 CT: " 85,87,90 NM 85,91 CFT: " 87,90 NM 85,91 MCF: # 85,90 Kaolin-activated TEG differentiated between severe FVIII-deficient patients with and without inhibitors 92 Treatments guided by VETs:…”
Section: Hemophilias and Acquired Factor Deficiencies (Viii And Ix)mentioning
confidence: 99%